Association of the uric acid-to-HDL cholesterol ratio with incident type 2 diabetes in community-dwelling older adults in China: a retrospective cohort study - Sun, Heping; Zhong, Shao; Wang, Zhaoxiang; Wang, Qianqian; Lu, Bing (Frontiers in Endocrinology, 2026)
ObjectiveThe serum uric acid-to-high-density lipoprotein cholesterol ratio (UHR) is considered an emerging indicator of inflammatory and metabolic disorders. The aim of this research is to assess the link between UHR and the susceptibility to type 2 diabetes among elderly people in Chinese communities.MethodsA retrospective cohort study was conducted. The participants were elderly non-diabetic individuals who underwent annual health check-ups in the Kunshan community, China, from January 2018 to December 2023. A multivariable Cox proportional hazards model was used to investigate the relationship between baseline UHR levels and the incidence of type 2 diabetes in the elderly population.ResultsAfter a median follow-up of 3.88 years, 773 type 2 diabetes events were recorded among the 7525 elderly non-diabetic individuals. After adjustment for confounders, each 1–standard deviation (SD) increase in the UHR was associated with a higher risk of type 2 diabetes (HR = 1.156, 95% CI 1.069-1.250, P < 0.001), even within the normal UHR range. The relationship between UHR and type 2 diabetes risk is more pronounced in non-obese individuals.ConclusionIn Chinese community-dwelling elderly individuals, baseline UHR levels are associated with the risk of developing type 2 diabetes. Monitoring UHR levels might help predict and assess the risk of type 2 diabetes.